Palladio Optimization Suite: QoS optimization for component-based Cloud applications - Ciavotta, Michele; Ardagna, Danilo; Koziolek, Anne (EAI Endorsed Transactions on Cloud Systems, 2016)
One important issue in software engineering is to find an effective way to deal with the increasing complexity of software computing system. Modern software applications have evolved in terms of size and scope. Specific tools have been created to predict the Quality of Service (QoS) at design-time. However, the optimization of an architecture usually has to be done manually, resulting in an arduous and time-consuming process. For this reason, we present the Palladio Optimization Suite (POS), a collection of complementary plugins realized to run atop Palladio Bench with the aim of automatizing the exploration of the space of possible architectures by means of advanced search paradigms.